CORPORATE GOVERNANCE MEMODERASI PENGARUH FINANCIAL PERFORMANCE, ENVIRONMENTAL PERFORMANCE DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Ramadani, Putri; Wijaya, Ronni Andri; Putra, Ramdani Bayu; Lusiana, Lusiana (PUBLIKASI RISETMAHASISWA AKUNTANSI, 2023)
This study aims to examine the Effects of Financial Performance, Environmental Performance and Tax Avoidance on Corporate Values ​​with Corporate Governance as a moderating variable in Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. The sample selection technique in this study used porpusive sampling and obtained 29 companies as research samples. The method of analysis uses regression moderation analysis with Eviews 10. Based on the results of hypothesis testing it was found that Financial Performance has a significant effect on Firm Value in Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. Environmental Performance has no significant effect on the Firm Value (NP) of Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. Tax Avoidance has a significant effect on the Company Value of Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. Financial Performance has no significant effect on Corporate Value with Corporate Governance as a moderation for Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. Environmental Performance has a significant effect on Company Value with Corporate Governance as a moderation for Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021. Tax Avoidance has no significant effect on Corporate Value with Corporate Governance as a moderation for Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2021.